Patients with familial biparental hydatidiform moles have normal methylation at imprinted genes - El Maarri, Osman (2005)
In molar tissues from patients with recurrent biparental hydatidiform moles, we could previously demonstrate that differentially methylated regions (DMRs) of four imprinted genes are abnormally methylated on the maternal alleles. It remained unclear if this abnormal methylation originated de novo in the molar tissues or if it is even recognizable in the patient somatic tissues. To address this question, we investigated the DNA methylation of four imprinted genes in total blood from the two sister-patients. Here, we show that both patients retain normal methylation levels at the DMRs of the four genes in blood tissues. For two maternally expressed genes, we could use informative SNPs to follow the inheritance of the abnormally methylated maternal alleles in the molar tissues. We find that the transmitted abnormally methylated maternal alleles to the moles originated from the maternal grandmother and that the same alleles are not methylated in the patients. Our data suggest that the abnormal methylation in familial biparental molar tissues was acquired de novo in the patients’germline as a result of a false reprogramming or during the postzygotic development of the conceptuses that led to moles.